Proyeksi Kebutuhan Air Minum Kecamatan Kuala Kampar Kabupaten Pelalawan Sampai Tahun 2038 - Siahaan, Jessica; Asmura, Jecky; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Drinking water is one of the basic necessities for the quality and sustainability of human life. Until now, the population uses water sourced from refill water / bottled water by 21%, wells by 29% and rain water by 50% as the main source of drinking water whose quality and quantity are not guaranteed. The need for drinking water from domestic and non-domestic needs or also known as adequate water for basic human needs and other activities that require water. The need for drinking water in Kuala Kampar District is calculated based on population projections using three methods and the chosen method is the arithmetic method. From the results of these calculations, it can be estimated that the population in the sub-district will reach 14.194 people in 2038. So that domestic water needs are 8,88 liters / second and non-domestic water needs are 1,33 liters/second. So that the total water requirement is 10,21 liters/second. Keywords: Kuala Kampar, pertumbuhan penduduk, proyeksi kebutuhan air minum.